Typological peculiarities of empathic interpersonal interaction in adolescence - Kolomiets, Tatiana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article consider the empathic interpersonal interaction as one of perspective form of personality coexistence in dyad "Me-Other". The results of empiric research of integral empathy and empathic interpersonal interaction in adolescence are presented. The age, gender and dynamic peculiarities of researched phenomenon were analysed. It is shown that in the period of late adolescence the effective forms of empathy (consonance and dissonance) are more inherent to young men and for girls – sensual. It is proved that for the development of integral empathy in adolescence in the transition from early to late adolescence the intensive (abrupt) dynamic is typical for the girls and moderate (light) for the boys. It is established that for the development of empathic interpersonal interaction the adolescence is relatively stable: dynamic is moderate and gender differences mainly insignificant. The most widespread in adolescence is promoted empathic interpersonal interaction. Less frequently young people resort to realization of altruistic interaction. The least inherent for the young people is egocentric and subject centric interaction.